Analisis Pertumbuhan Laba pada PT. Bank UOB: Pendekatan Berdasarkan analisis tren dan Rasio Keuangan Tahun 2019-2023 - Sabrina, Siti Nabila Zida; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
Financial performance is a key indicator that reflects the operational success and stability of a bank. This study analyzes the profit growth trend and profitability ratios of PT Bank UOB Indonesia during the 2019-2023 period using the Least Square method. using the Least Square method. The results showed significant fluctuations in net profit. This research highlights the importance of more efficient asset management, integrated financial strategies, and strengthened risk management to improve profitability and support growth. risk management to improve profitability and support sustainable growth. sustainable growth. This article provides insights for management and stakeholders stakeholders in making strategic decisions to improve financial performance and and competitiveness in the banking sector. The company's Return on Assets (ROA) ratio during the period was in the fairly healthy category, with values ​​ranging from 0.61% to 0.87%. Although fairly healthy, this ROA is still below the healthy category standard (>1.25%), indicating that the efficiency of asset use in generating profits needs to be improved.